P0350THE DURATION OF PROTEINURIA REMISSION AND CLINICAL OUTCOMES IN IGA NEPHROPATHY. (6th June 2020) - Canney, Mark; Barbour, Sean; Zheng, Sophia; Coppo, Rosanna; Zhang, Hong; Liu, Zhi Hong; Matsuzaki, Keiichi; Suzuki, Yusuke; Katafuchi, Ritsuko; Reich, Heather; Cattran, Daniel C
Abstract: Background and Aims: A relative reduction in proteinuria has been proposed as a surrogate outcome for therapeutic trials in IgA nephropathy. It is currently unknown how long a reduction in proteinuria needs to be maintained in order to mitigate the long-term risk of disease progression. To address this knowledge gap we sought to quantify the association between duration of proteinuria remission and the risk of disease progression in IgA nephropathy. Method: In this retrospective multi-ethnic international cohort of adult patients with biopsy-proven IgA nephropathy, we defined proteinuria remission based on three criteria: (i) peak proteinuria on/after biopsy ≥1g/day; (ii) an absolute reduction in proteinuria to <1g/day; (iii) a ≥25% reduction in proteinuria from the peak value. The exposure of interest was the total duration of first remission, treated as a time-varying covariate using longitudinal proteinuria measurements. The primary outcome was the occurrence of end-stage kidney disease or a sustained 50% reduction in estimated glomerular filtration rate (eGFR). The association between duration of remission and the primary outcome was visualized using restricted cubic splines, and quantified using extended Cox proportional hazards regression models. Results: A total of 1864 patients met criteria for remission, which occurred a median of 8.3 months after biopsy (IQR 3.6-22). They had a median age of 36.8 (IQR 29.4-46.6) years and a median eGFR of 78 (IQR 55-104) mL/min/1.73m 2 . Median proteinuria was 1.54 (IQR 1.09-2.4) g/day at the time of biopsy and 0.55 (IQR 0.33-0.76) g/day at the time of entering remission. During a median follow-up of 3.9 years, 274 patients (14.7%) experienced the primary outcome. The relationship between duration of proteinuria remission and the primary outcome was non-linear (Figure). Each 3 months in sustained remission up to 51 months was associated with an additional 9% reduction in the risk of disease progression (hazard ratio 0.91, 95% confidence interval 0.89-0.93). In contrast, each additional 3 months in remission beyond 51 months was associated with a smaller non-significant risk reduction (hazard ratio 0.99, 95% confidence interval 0.96-1.03). These finding were robust to multivariable adjustment and were consistent across subgroups based on the MEST histology score, and whether or not the remission occurred while on renin-angiotensin-aldosterone-system blockade or after immunosuppression treatment. Results were similar when relapse was defined as either a 50% or 100% increase in proteinuria from the nadir value after remission to an absolute value of ≥1g/day. Conclusion: We observed a strong non-linear dose-response relationship between the duration of proteinuria remission and the risk of disease progression in patients with IgA nephropathy. The ability to quantitate the renal survival benefit related to the duration of remission is an important advance for patients and their physicians. Rather than there being a minimum duration of proteinuria remission in IgA nephropathy, our results demonstrate that even short durations in remission, or small increases in remission duration, are both associated with significant reductions in the risk of disease progression. For future therapeutic trials in IgA nephropathy using proteinuria as a surrogate outcome, our findings illustrate the need to consider the duration of proteinuria reduction, in addition to the magnitude of proteinuria reduction, when evaluating the anticipated treatment effect on long-term clinical endpoints.